Front Cover: Halide‐Substituted Phosphacyclohexadienyl Iron Complexes: Covalent Structures vs. Ion Pairs (Eur. J. Inorg. Chem. 11‐12/2019). Issue 11 (8th March 2019) - Hoidn, Christian M.; Leitl, Julia; Ziegler, Christoph G. P.; Shenderovich, Ilya G.; Wolf, Robert
Abstract : The Front Cover shows a general molecular structure for the first transition metal complexes bearing π‐coordinated λ 3 ‐halophosphacyclohexadienyl ligands. A thorough comparison of their spectroscopic properties and computational data indicates the presence of polarized P–halogen bonds. The heavier halogen atoms have an increasing tendency to dissociate, leading to the formation of ionic structures. This situation is illustrated by a paddle ball game: depending on the size of the ball, the elastic string may snap, resulting in the separation of paddle and ball. More information can be found in the Full Paper by R. Wolf et al. For more on the story behind the cover research, see the Cover Profile .